The Impact Of Organizational Culture Toward Organizational Competitiveness At Pt. Goenta Jaya Medan - Javerson Simamora; Eddy Gunawan; Felix Leonardi; Elyzabeth Wijaya; Ester (Jurnal Kolaboratif Sains, 2026)
The purpose of this research is to analyze the impact of organizational culture toward competitiveness at PT. Goenta Jaya Medan, the data is obtained through interview and questionnaire. There are 32 respondents from the company which only work in the office and supervisor only in company. Whereby the data analysis using descriptive statistic (mean, median, mode), validity, reliability, coefficient of correlation, regression analysis and hypothesis test. The result from the data is all valid, reliable and normal. so the data can be used for further analyze. There has a significant impact the organizational culture toward organizational competitiveness, where Ha accepted and Ha rejected Zcount = 4.776> Ztable = 1,96. Determination (r2) = 85.6% prove that organizational culture impact 85.6% toward organization competitiveness. The writer intends to give some recommendations which are outbound, happy weekend, monthly meeting and open-minded discussion, switching work day and give appreciation and recognition.